Memnoniella mohanramii sp. nov. and Zygosporium anupamvarmae sp. nov. from India - and K. SHARATH BABU, C. MANOHARACHARY*, D. K. AGARWAL, G. SURESHKUMAR, I.K. KUNWAR (Indian Phytopathology, 2006)
During a survey of microfungi from Andhra Pradesh, two new anamorphic fungi were discovered viz. Memnoniella mohanramii sp. nov. with ellipsoidal, smooth conidia and Zygosporium anupamvarmae sp. nov. having broadly falcate conidia with 2-5 ridge like striations. Such type of conidia are not described in any of the known species of these genera hence reported as new taxa.